The Charging of Administrative Fee for Customers of Mudharabah Saving Depositors - Muhammad, Danang Wahyu; Mustika, Mega (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2019)
One of the saving products in Islamic banks is mudharabah. In the practice of mudharabah saving, there are Islamic banks charge an administrative fee and some do not. The research aims to clarify the fiqh basis of the charge of administrative fees to Shahibul Maal by mudharib in mudharabah saving. This normative research used secondary data consisting of primary, secondary, and tertiary legal materials. It is found that the charge of administrative fee by mudharib to Shahibul Maal on mudharabah saving does not have a clear foundation in fiqh. Based on the Fatwa of the National Sharia Board (DSN), the operational cost of mudharabah savings is the responsibility of the Mudharib and not the Shahibul Maal, since the Shahibul Maal has provided the fund. Mudharib can charge for the operational cost only if there is an agreement with the Shahibul Maal.